The Representation of Gender in “Kalidar” - M. Paknia; M. Sadeghi Pouya (Taḥqīqāt-i Farhangī-i Īrān)
This article is to represent the linguistic indicators of gender in, Kalidar, the longest Persian novel. In this work of art, which is not so far from an anthropological report, women have an important and complicated place. Despite of a fundamental role they play in different aspects of daily life, Kalidar women are humiliated under literary gender clichés. The novel is full of proverbs and ironies which have been commonplace in vulgar Persian language for ridiculing and despising femininity. Our main question is: what is the place of women in Kalider from the point of view of a moderate feminism? And our hypothesis is that there is a paradoxical position for women in this novel. On one hand, they are represented as a source of life for men and for all of the family and thereby for the whole community, in some extent, because of the very particular life style of nomadic people, and on the other hand, they have a sense of insult and contempt, due to the general treatment whit women in almost every pre modern community. It means that those clichés have not been deducted from a low role of women in real life, but are constructed by a sexist culture.